Countermeasures for Environmental Damage Caused by Drilling Water Sources for The Mineral Water Industry - Hafid, Raden Bagus Mochammad Ramadhan Razief; Sahrudin, Sahrudin; Farid, Ahmad (CV. Pustaka Parawali, 2024)
The mineral water industry has grown rapidly in recent decades, as people have become more aware of the importance of quality drinking water. However, overexploitation of groundwater to meet the needs of this industry can cause significant environmental damage. This abstract discusses various measures that can be taken to mitigate environmental damage due to the drilling of water sources for the mineral water industry. One of the main solutions is to implement stricter regulations related to groundwater extraction. This includes limiting the amount of water that can be withdrawn by mineral water companies, as well as implementing higher water quality standards. The government also needs to conduct stricter supervision of mineral water industry activities to ensure compliance with applicable regulations. Another important effort is to encourage the use of more environmentally friendly technologies in the water intake and treatment process. For example, the use of reverse osmosis systems that are more water-efficient than conventional methods. The mineral water industry also needs to educate the public about the importance of preserving the environment, and encourage community participation in efforts to conserve water resources. In addition, it is important to develop alternative water sources for the mineral water industry, such as treated surface water or seawater. This can help reduce the pressure on.